2001
DOI: 10.1093/her/16.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Empowering counseling--a case study: nurse-patient encounter in a hospital

Abstract: This study illustrates practices that a nurse uses in order to empower patients. The emphasis is on speech formulae that encourage patients to discuss their concerns and to solicit information about impending surgery. The study is a part of a larger research project and a single case was selected for presentation in this article because it differed from the rest of the data by manifesting empowering practice. A videotaped nurse-patient health counseling session was conducted in a hospital and transcribed verba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 28 publications
2
42
0
2
Order By: Relevance
“…Being video recorded might have affected both the pupils and the nurses, leading to a different performance. However, when watching parts of the recordings afterwards, both the pupils and the nurses described the presence of the researcher and camera as having affected the encounter only negligibly, as also confirmed in earlier studies [28,37,38]. The health dialogues took place within the same county in Sweden, and the nurses worked with similar health and lifestyle tools, which may have affected the results.…”
Section: Limitationssupporting
confidence: 66%
“…Being video recorded might have affected both the pupils and the nurses, leading to a different performance. However, when watching parts of the recordings afterwards, both the pupils and the nurses described the presence of the researcher and camera as having affected the encounter only negligibly, as also confirmed in earlier studies [28,37,38]. The health dialogues took place within the same county in Sweden, and the nurses worked with similar health and lifestyle tools, which may have affected the results.…”
Section: Limitationssupporting
confidence: 66%
“…The interaction layout of guided exercise sessions allowed for a more reciprocal relationship between the older adults and the physiotherapists than did the structured approach. Bilateral and reciprocal health care encounters have been defined as empowering to clients (Collins, Drew, Watt, & Entwistle, 2005;Kettunen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated interwoven dimensions of building trust and meaning, connecting, caring, mutual knowledge, and mutual creating. This is supported by Kettunen, Poskiparta, and Liimatainen (2001), who found that, during empowering counseling in a hospital, the encounters began by developing a reciprocal relationship between a nurse and a patient, to be followed by tactful exploration of patient needs, together with active power sharing, listening, and, finally, by building up a positive vision of the future. These findings confirm Wallerstein's (2006) notion of the components of the empowering health promotion, where personal skills are developed in a supportive environment, with information being shared in dialog with professionals and peers, and where clients are encouraged to participate in the planning and implementation of the intervention.…”
Section: Group-based Exercise In Frail Older Adultsmentioning
confidence: 92%
“…Only physiotherapists and psychologists utilised more participative and activating methods that are needed when the aim is adult learning (33)(34)(35)(36)(37)(38). Furthermore, longer work experience in OHS seems to broaden the scope of educational activities in terms of clients, situations, and content of health education, but the methods stay the same.…”
Section: Discussionmentioning
confidence: 99%